2002
DOI: 10.3354/meps242275
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale three-dimensional spatial use by diving, lactating female Weddell seals Leptonychotes weddellii

Abstract: Despite the importance of fine-scale spatial use in understanding an animal's foraging ecology, these data cannot readily be collected for free-ranging marine mammals. We used an acoustic positioning system to quantify, for the first time, the fine-scale 3-dimensional (3D) spatial use of free-ranging Weddell seals swimming under ice. Unlike many other phocid species, lactating Weddell seals spent up to 25% of their time diving. Given the limited foraging range imposed on the seals by the fast ice upon which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 47 publications
6
69
0
Order By: Relevance
“…The diving behavior of Weddell seals, including lactating females as well as nursing, weaned, and yearling animals, has been extensively investigated with time-depth recorders, or TDRs, including satellite-uplinked instruments (e.g., Kooyman, 1967;Testa et al, 1989;Burns et al, , 1999Castellini et al, 1992;Sato et al, 2002Sato et al, , 2003Williams et al, 2004;Fuiman et al, 2007). The recent development of instrumentation that records directional information ( Harcourt et al, 2000;Davis et al, 2001;Hindell et al, 2002;Mitani et al, 2003) allows examination of dive behavior in three-dimensional space. Although food intake requires diving, even deep diving need not entail food consumption.…”
Section: Monitoring Food Consumption During the Lactation Periodmentioning
confidence: 99%
“…The diving behavior of Weddell seals, including lactating females as well as nursing, weaned, and yearling animals, has been extensively investigated with time-depth recorders, or TDRs, including satellite-uplinked instruments (e.g., Kooyman, 1967;Testa et al, 1989;Burns et al, , 1999Castellini et al, 1992;Sato et al, 2002Sato et al, , 2003Williams et al, 2004;Fuiman et al, 2007). The recent development of instrumentation that records directional information ( Harcourt et al, 2000;Davis et al, 2001;Hindell et al, 2002;Mitani et al, 2003) allows examination of dive behavior in three-dimensional space. Although food intake requires diving, even deep diving need not entail food consumption.…”
Section: Monitoring Food Consumption During the Lactation Periodmentioning
confidence: 99%
“…/j.dsr2.2006 VHF telemetry (Hooker et al, 2002 and references therein), satellite tracking telemetry (Ferraroli et al, 2004;Hays et al, 2004a;Jouventin and Weimerskirch, 1990;Sims et al, 2005), GPS technology (Weimerskirch et al, 2005), and geolocation or global location sensing (e.g., Block et al, 2001;Hill, 1994;Wilson et al, 1994). Only two methods work underwater, these being acoustic telemetry (e.g., Hindell et al, 2002) and dead-reckoning (Wilson and Wilson, 1988). Acoustic telemetry necessitates that receivers be within a few hundred metres of the animal to be tracked so that fast and widely ranging species are difficult to access with this method.…”
Section: Introductionmentioning
confidence: 99%
“…The diving habits of the Weddell seal Leptonychotes weddellii have been well studied using time-depth recorders and satellite-linked, time-depth recorders (Kooyman 1981, Castellini et al 1992, Testa 1994, acoustic tracking (Harcourt et al 2000, Hindell et al 2002, dead reckoners (Davis et al 1999(Davis et al , 2003, and geomagnetic and acceleration recorders (Mitani et al , 2004. These seals are highly adapted for hunting in the cold, dark, ice-covered waters of Antarctica (Kooyman 1981, Castellini et al 1992.…”
Section: Introductionmentioning
confidence: 99%
“…Marshall 1998, Davis et al 1999, Fuiman et al 2002, Hooker et al 2002, Sato et al 2002, Watanabe et al 2003. These methods have already shown that some of the previous inferences about foraging behavior were incorrect (Lesage et al 1999, Davis et al 2003.The diving habits of the Weddell seal Leptonychotes weddellii have been well studied using time-depth recorders and satellite-linked, time-depth recorders (Kooyman 1981, Castellini et al 1992, Testa 1994, acoustic tracking (Harcourt et al 2000, Hindell et al 2002, dead reckoners (Davis et al 1999(Davis et al , 2003, and geomagnetic and acceleration recorders (Mitani et al , 2004. These seals are highly adapted for hunting in the cold, dark, ice-covered waters of Antarctica (Kooyman 1981, Castellini et al 1992.…”
mentioning
confidence: 99%